THE MEANING OF FAMILY IN THE QURAN: SEMANTIC STUDY OF THE WORD AHL, ‘ASYI<RAH, RAHTHU, A<LU, QURBA<, AND RUKNU
The Central Agency on Statistics states that the divorce rate in Indonesia has increased significantly after the pandemic. Indonesia has the largest Muslim majority population in the world, obviously, being a role model for the Muslim World, including in terms of family management. Thus, it is important for Muslims to know the meaning of family mentioned in the Qur’an in order to create harmonization in the household to reduce the divorce percentage. This study uses a qualitative method which is library research with primary sources in the form of the al-Qur’an and classic linguistic books (kutub al-syu’ara>’), while secondary sources in the form of dictionaries (qa>mus) such as Lisa>n al-Araby, Asa>s al-Balaghah, and other supporting sources. This study uses the theory of al-wuju>h wa al-nazha>ir to examine the extent to which the differences in the meaning of the vocabulary in the Qur’an. The results of the study show that there are 6 words in the Qur’an that have family meanings, namely ahl, ‘asyi>rah, rah